Potentiostatic Oxide Growth Kinetics on Ni-Cr and Co-Cr Alloys: Potential and pH Dependences. (20th April 2015) - Musa, Ahmed Y.; Behazin, Mehran; Wren, Jungsook Clara
Abstract: Oxide growth kinetics on the Ni-Cr-Fe alloy Inconel 600 and the Co-Cr alloy Stellite 6 under potentiostatic polarization have been investigated by current measurements augmented by ex-situ surface analyses. The results reveal a mechanism for metal oxidation and oxide formation that is common to both alloys. The reaction thermodynamics for the oxidation of a metal determine whether a certain metal oxidation can or cannot occur. However, the metal oxidation proceeds via two competing pathways, oxide formation and metal ion dissolution. At pH 10.6 where the solubilities of Fe II, Ni II or Co II species are near their minima, oxide formation is favoured over metal ion dissolution. As the oxide grows, the rate of metal oxidation decreases with time due to an increase in the electrochemical potential barrier. The oxide formation occurs sequentially; the conversion of the preformed Cr2 O3 film to chromite (FeCr2 O4 or CoCr2 O4 ) proceeds before the next layers of Fe3 O4 /NiFe2 O4 and NiO/Ni(OH)2 grow on Inconel 600, or CoO/Co(OH)2 grows on Stellite 6. The effect of a different EAPP is to limit the oxidation sequence. The pH does not directly affect the driving force for metal oxidation but it strongly influences the relative rates of oxide formation and metal dissolution, thereby affecting metal oxidation kinetics.